Determinan Return on Asset Pada Perusahaan Subsektor Pertambangan Batubara Yang Terdaftar di Bursa Efek Indonesia - Edisah Putra Nainggolan (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study aims to determine the determinants of Return on Assets in mining sector companies listed on the Indonesian stock exchange. The factors that become the object of research are the Current Ratio, Debt to Equity Ratio and Asset Structure. The research approach uses an associative approach. The sampling criteria used purposive sampling technique, namely the determination of the sample with certain criteria, so that of the 21 companies that became the population there were only 9 companies that could be sampled in the Coal Mining companies listed on the Indonesia Stock Exchange. Data collection techniques using documentation studies. The data analysis technique used multiple linear regression, regression requirements test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), hypothesis testing (t test and F test) and the coefficient of determination (R-square). Processing data in this study using SPSS Software (Statistical Product and Service Solution) 16 for Windows. The results of the study prove that partially Current Ratio has a significant effect on Return On Assets, Debt to Equity Ratio has a significant effect on Return On Assets, and Asset Structure has a significant effect on Return On Assets. Meanwhile, simultaneously Current Ratio, Debt to Equity Ratio and Asset Structure have a significant effect on Return On Assets